2023
DOI: 10.3389/fendo.2023.1114963
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between fat distribution in central region and comorbidities in obese people: Based on NHANES 2011–2018

Abstract: BackgroundCentral obesity is closely related to comorbidity, while the relationship between fat accumulation pattern and abnormal distribution in different parts of the central region of obese people and comorbidity is not clear. This study aimed to explore the relationship between fat distribution in central region and comorbidity among obese participants.MethodsWe used observational data of NHANES 2011–2018 to identify 12 obesity-related comorbidities in 7 categories based on questionnaire responses from par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Amongst the included studies, six articles examined the association between VAT-to-SAT ratio and blood pressure (BP) [ 15 , 23 , 31 – 34 ], 9 studies examined atherosclerosis indices [ 24 , 35 42 ], 10 studies examined CVDs events [ 26 , 43 51 ] and remaining two studies assessed CVDs risk scores [ 25 , 52 ]. Among the reviewed studies, eleven were conducted in Japan [ 26 , 31 , 33 , 36 , 38 , 39 , 41 , 43 , 47 , 48 , 51 ], six in USA [ 15 , 40 , 42 , 44 , 49 , 52 ], three in Brazil [ 25 , 35 , 45 ], three in China [ 24 , 34 , 50 ], two in South Korea [ 23 , 32 ], one in Netherlands [ 37 ], and one in Portugal [ 46 ]. The characteristics and quality scores of the included studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Amongst the included studies, six articles examined the association between VAT-to-SAT ratio and blood pressure (BP) [ 15 , 23 , 31 – 34 ], 9 studies examined atherosclerosis indices [ 24 , 35 42 ], 10 studies examined CVDs events [ 26 , 43 51 ] and remaining two studies assessed CVDs risk scores [ 25 , 52 ]. Among the reviewed studies, eleven were conducted in Japan [ 26 , 31 , 33 , 36 , 38 , 39 , 41 , 43 , 47 , 48 , 51 ], six in USA [ 15 , 40 , 42 , 44 , 49 , 52 ], three in Brazil [ 25 , 35 , 45 ], three in China [ 24 , 34 , 50 ], two in South Korea [ 23 , 32 ], one in Netherlands [ 37 ], and one in Portugal [ 46 ]. The characteristics and quality scores of the included studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…These two factors reinforce each other through a vicious cycle, causing excessive nutrient synthesis, cellular growth, homeostatic breakdown, and disease development. Our previous research also systematically showed a close relationship between adipose accumulation, inflammation, and comorbidities such as cardiovascular diseases in individuals with obesity [ 28 ]. Similarly, Dugani et al [ 29 ] found a significant correlation between lipid, inflammatory, and metabolic biomarkers and the risk of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to several previous studies, our ndings showed that lower serum levels of vitamin D were not associated with hip circumference or gynoid fat (69, 72, 73). It has been claimed that the risk of CVD is inversely associated with increased gynoid fat, despite android fat mass (74,75). This nding has been linked to gynoid adipocyte-enhanced lipoprotein lipase activity and more e cient free fatty acid accumulation compared to visceral adipocytes (76).…”
Section: Discussionmentioning
confidence: 99%